2012
DOI: 10.1002/jat.2785
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate induces apoptosis in lung cancer A549 cells through reactive oxygen species‐mediated mitochondrion‐dependent pathway

Abstract: Perfluorooctane sulfonate (PFOS) is a widespread environmental contaminant that is detected in the lung of mammals. The mechanisms underlying PFOS-induced lung cytotoxicity remain unclear. The main purpose of this study was to evaluate the cytotoxic effects of PFOS on human lung cancer A549 cells and its possible molecular mechanism. A549 cells were treated with PFOS (0, 25, 50, 100 and 200 μm) and the cellular apoptosis, mitochondrial membrane potential as well as intracellular reactive oxygen species were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 48 publications
4
12
0
3
Order By: Relevance
“…Furthermore, we observed that PFOS induced a decrease in GSH level, and an increase in MDA level and SOD in a dose-depend manner. It is consistent with another description in lung cancer A549 cells [50] . According to previous studies, the level of MDA reflects the degree of radical lipid peroxidation in cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we observed that PFOS induced a decrease in GSH level, and an increase in MDA level and SOD in a dose-depend manner. It is consistent with another description in lung cancer A549 cells [50] . According to previous studies, the level of MDA reflects the degree of radical lipid peroxidation in cells.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, PFOS-induced apoptosis was raised in a dose-dependent manner. Previous studies have also shown the PFOS-induced apoptosis in lung cancer A549 cells and cerebellar granule cells [49] , [50] . These, along with our results, indicate that apoptosis is an important factor in the cytotoxicity of PFOS.…”
Section: Discussionmentioning
confidence: 73%
“…Cell apoptosis is a highly regulated process of programmed cell death that is important for modulating cell numbers ( Fiers et al ., 1999 ; Fadeel and Orrenius, 2005 ). Many intrinsic and extrinsic factors, especially caspases ( Fuchs and Steller, 2011 ; Mao et al ., 2013 ) and Bcl-2 superfamily proteins ( Martinou and Youle, 2011 ) regulate apoptosis ( Fuchs and Steller, 2011 ). PQ has been reported to induce apoptosis in some mammalian cells ( Cappelletti et al ., 1998 ; Li and Sun, 1999 ; Rio and Velez-Pardo, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 ). The mitochondria, a critical intracellular organelle, plays an essential role in the regulation of apoptosis ( Green and Kroemer, 2004 ; Orrenius, 2004 ; Mao et al ., 2013 ). ROS-induced MMP depolarization is involved in apoptosis related to mitochondrial dysfunction ( Chipuk et al ., 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation